1993
DOI: 10.1677/joe.0.1390235
|View full text |Cite
|
Sign up to set email alerts
|

Rat placental lactogen-I binds to the choroid plexus and hypothalamus of the pregnant rat

Abstract: Recent findings suggest that placental lactogen has a role in the regulation of hypothalamic function during pregnancy. To explore the mechanisms by which placental hormones may exert effects in the maternal central nervous system, we have examined the binding of rat placental lactogen-I (rPL-I) to brain slices from pregnant rats at mid- and late gestation. The binding of rPL-I to maternal rat brain was compared with that of human GH (hGH). Radiolabelled rPL-I bound specifically to ependymal cells of the choro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The binding data are still somewhat complicated by the substantial binding of prolactin/growth hormone to several members of the growth hormone/ prolactin receptor superfamily. Interesting recent data on the binding of lactogenic ligands related to prolactin to the prolactin receptor suggest that other ligands prominent in pregnancy are also likely to interact importantly with this superfamily of receptors Kelly et al, 1991;Pihoker et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The binding data are still somewhat complicated by the substantial binding of prolactin/growth hormone to several members of the growth hormone/ prolactin receptor superfamily. Interesting recent data on the binding of lactogenic ligands related to prolactin to the prolactin receptor suggest that other ligands prominent in pregnancy are also likely to interact importantly with this superfamily of receptors Kelly et al, 1991;Pihoker et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…PRL as well as rPL-I appear to bind to epi thelial cells of the choroid plexus; their binding can be blocked by the addition of excess lactogenic hormones [8,22,23], Once in the CSF and past the blood-CSF barrier, rPL-I and rPL-II can simply diffuse into neuropil adjacent to or near the ventricles, e.g. the MPOA.…”
Section: Discussionmentioning
confidence: 99%
“…While it is unknown whether rPLs act at neural sites other than the MPOA to affect maternal behavior, the actions of rPLs after MPOA infu sions are probably not due to the diffusion of rPLs to oth er areas of the brain. Similar doses of oPRL which stimu late maternal behavior when infused into the MPOA do not affect maternal behavior when infused into the ven tricular system [3], Other support for the MPOA as a site of rPL action is the recent work of Pihoker et al [8] who reported in vitro binding of radiolabeled rPL-I to the MPOA, hypothalamus, and choroid plexus. Interestingly, the region of the MPOA which appeared maximally responsive to rPL-I and rPL-II stimulation of maternal behavior in the present study was at 7.8 to 8.0 in the AP plane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings establish that during pregnancy, rPL-11, and possibly rPL-I, which is secreted between days 10 and 13 of gestation, gain access to the CSF. Additional support for the concept that rPLs are transported into the CSF from blood during gestation is the recent finding that rPL-I binds to the choroid plexus in female rats (58). Interestingly, in women, human chorionic gonadotrophin (hCG) and human placental lactogen (hPL) are detectable in CSF during pregnancy (59).…”
Section: Role Of Other Lactogenic Hormones In the Induction Of Maternmentioning
confidence: 94%